2013
DOI: 10.1158/1078-0432.ccr-12-2549
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Molecular Secrets of Inflammatory Breast Cancer Biology: An Integrated Analysis of Three Distinct Affymetrix Gene Expression Datasets

Abstract: Background: Inflammatory breast cancer (IBC) is a poorly characterized form of breast cancer. So far, the results of expression profiling in IBC are inconclusive due to various reasons including limited sample size. Here, we present the integration of three Affymetrix expression datasets collected through the World IBC Consortium allowing us to interrogate the molecular profile of IBC using the largest series of IBC samples ever reported.Experimental Design: Affymetrix profiles (HGU133-series) from 137 patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
172
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 132 publications
(183 citation statements)
references
References 37 publications
7
172
0
Order By: Relevance
“…Obesity has been related to inflammatory processes (20). In fact, inflammation and immune-related processes characterized the IBC tumor phenotype in an analysis of IBC's molecular profile (21). Moreover e-cadherin, which is overexpressed in IBC and accounts for the formation of tumor emboli, is increased in inflammation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been related to inflammatory processes (20). In fact, inflammation and immune-related processes characterized the IBC tumor phenotype in an analysis of IBC's molecular profile (21). Moreover e-cadherin, which is overexpressed in IBC and accounts for the formation of tumor emboli, is increased in inflammation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular profiling studies indicate that IBC is a molecularly distinct subtype of breast cancer, providing preliminary insight into clinically relevant pathways that influence IBC tumorigenesis (10). For example, HER2 is commonly amplified or overexpressed in IBC (11), whereas genes typically overexpessed in non-IBC: TGFb, progesterone receptor, and the estrogen receptor (ER) are typically downregulated in IBC (12). While previous biomarker studies offer insight into IBC, IBC analyses are typically limited to a subset of target molecules or pathways.…”
Section: Introductionmentioning
confidence: 99%
“…No consistent gene signature associated with IBC has been validated (4). Recently, it has been showed that IBC is transcriptionally heterogeneous and that all molecular subtypes described in non-IBC are detectable in IBC, albeit with a different frequency (5).…”
Section: Introductionmentioning
confidence: 99%